Hypoxic-Ischemic Brain Damage in 7-Days-Old Rats: Early Neuronal Changes and the Long-Term Outcome - Ota Nakasone, Arturo (1999)
OBJECTIVES: To study the changes after hypoxia-ischemia (HI), and to observe both, the vulnerability of the different regions of the brain to HI and the heat shock protein-72 kDa (HSP72) induction and its efects on the neuronal cell. MATERIAL AND METHODS: 7-days-old rats were exposed to left carotid artery ligation followed by 2 h of HI and then they were sacrificed at different time points. Brains extracted at 1-72 h were immunohistochemically study using the HSP-72 and the microtubule associated protein-2 (MAP2) stainings. Brains extracted at 1-4 weeks underwent histopathological study. RESULTS: Loss of MAP2 immunostaining was detected since the 1st hour post-insult, being highest at 24 h. MAP2 reappeared at 72 h in almost all the brain regions of the ligated hemisphere, except the hippocampal CA3 region. At 1-2 weeks post HI, we observed atrophic and cystic lesions. 15-20% of rats did not show any anatomical lesion up to 4 weeks post HI. The HSP72 synthesis was early in the dentate gyrus of the hippocampus, but a delayed induction was observed in the CA3 region; this region showed an increased vulnerability to HI. CONCLUSIONS: Absence of anatomical lesion was observed in 15-20% of rats exposed to HI. Atrophic or cystic lesions are observed since 1-2 weeks after the insult, despite an apparent immunohistochemical recovery at 72 h.